Biomimetic ZIF8 Nanosystem With Tumor Hypoxia Relief Ability to Enhance Chemo-Photothermal Synergistic Therapy - Zhao, Ziming; Liu, Zhaorong; Hua, Yabing; Pan, Yuanjie; Yi, Ge; Wu, Shengyue; He, Cong; Zhang, Yanzhuo; Yang, Yihua (Frontiers in Pharmacology, 2022)
Tumor hypoxic microenvironment can reduce the therapeutic effects of chemotherapy, radiotherapy, photodynamic therapy and immunotherapy etc. It is also a potential source of tumor recurrence and metastasis. A biomimetic nanosystem based on zeolitic imidazolate framework 8 (ZIF8), which had multifunctions of hypoxia relief, chemotherapy, and photothermal therapy, was established to improve tumor hypoxic microenvironment and overcome the corresponding therapeutic resistance. ZIF8 enveloped with DOX and CuS nanoparticles (DC@ZIF8) was synthesized by a sedimentation method. Red blood cell membrane and catalase (CAT) were coated onto DC@ZIF8 and biomimetic nanosystem (DC@ZIF8-MEMc) was formed. The designed DC@ZIF8-MEMc had a shape of polyhedral with an average particle size around 254 nm. The loading content of DOX, CAT and CuS was 4.9%, 6.2% and 2.5%, separately. The release of DOX from DC@ZIF8-MEMc was pH dependent and significantly faster at pH 5 due to the degradation of ZIF8. DC@ZIF8-MEMc exhibited outstanding photothermal conversion properties and excellent antitumor effect in vitro and in vivo. Moreover, the hypoxia relief by CAT was proved to have good sensitization effect on chemo-photothermal combined therapy. DC@ZIF8-MEMC is a prospective nanosystem which can realize great chemo-photothermal synergistic antitumor effect under the sensitization of CAT. The biomimetic multifunctional nanoplatform provides a potential strategy of chemo-photothermal synergistic antitumor effect under the sensitization of CAT.